2013
DOI: 10.1089/fpd.2012.1310
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Molecular Characterization ofVibrio choleraeO1, Non-O1 and Non-O139 in Tropical Seafood in Cochin, India

Abstract: The objective of this study was to determine the prevalence of O1, O139, and non-O1 and non-O139 Vibrio cholerae, which were associated with fresh and raw seafood samples harvested from Cochin, India waters during 2009-2011. Results from V. cholerae-specific biochemical, molecular, and serological assays identified five El Tor V. cholerae O1 Ogawa strains and 377 non-O1, non-O139 V. cholerae strains from 265 seafood samples. V. cholerae O139 strains were not isolated. Polymerase chain reaction assays confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Toxigenic non-O1/O139 serogroups have caused severe cholera-like outbreaks in India and other countries, including Haiti (Rudra et al, 1996 ; Dalsgaard et al, 1999 ; Onifade et al, 2011 ; Hasan et al, 2012 ). Two toxigenic V. cholerae O1 strains, positive for cholera toxin, have been isolated from Tilapia fish gill, harvested in sewage stabilization ponds in Tanzania and 5 O1 strains were isolated from two marine fish in Cochin, India during 2009–2011 (Kumar and Lalitha, 2013 ; Hounmanou et al, 2016 ). The presence of pathogenic serogroups O1 and O139 in fish scale samples collected in Mozambique have been detected by direct fluorescent antibody technique but the researchers were unable to culture them (Du Preez et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Toxigenic non-O1/O139 serogroups have caused severe cholera-like outbreaks in India and other countries, including Haiti (Rudra et al, 1996 ; Dalsgaard et al, 1999 ; Onifade et al, 2011 ; Hasan et al, 2012 ). Two toxigenic V. cholerae O1 strains, positive for cholera toxin, have been isolated from Tilapia fish gill, harvested in sewage stabilization ponds in Tanzania and 5 O1 strains were isolated from two marine fish in Cochin, India during 2009–2011 (Kumar and Lalitha, 2013 ; Hounmanou et al, 2016 ). The presence of pathogenic serogroups O1 and O139 in fish scale samples collected in Mozambique have been detected by direct fluorescent antibody technique but the researchers were unable to culture them (Du Preez et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…These isolates were collected in 2000 and 2001; the dissemination of this gene in environmental strains appeared later and so its non-detection in our strains was not surprising. Even though 29.5% (62/210) of non-O1/non-O139 V. cholerae isolated from tropical seafood in Cochin (India) in 2013 were resistant to cefpodoxime (Kumar and Lalitha, 2013 ), clearly, extended spectrum β-lactamase enzymes are uncommon in V. cholerae (Ceccarelli et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…V. cholerae O1, positive for cholera toxin gene, was isolated from Tilapia gills in Tanzania (Hounmanou, 2015 ). V. cholerae O1 isolates, positive to ctxA and tcpA genes were detected from two marine fish in Cochin, India (no details were given as to the fish species) (Kumar and Lalitha, 2013 ). In the same study, Kumar and Lalitha ( 2013 ) also identified 141 non-O1/O139 isolates from unidentified marine fish species (Table 1 ).…”
Section: Introductionmentioning
confidence: 99%